Statement of Prominent Political and Spiritual Leaders Given to the Movement for the Defense of the Hungarian Nation - Héderváry, Claire de (1962)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Movement for the Defense of the Hungarian Nation Strong words of support and encouragement from prominent political and spiritual leaders for the movement's cause.